Treatment of pain following cancer: applying neuro-immunology in rehabilitation practice. Issue 6 (13th March 2018) - Nijs, Jo; Leysen, Laurence; Pas, Roselien; Adriaenssens, Nele; Meeus, Mira; Hoelen, Wouter; Ickmans, Kelly; Moloney, Niamh
Abstract: Aim: Pain is the second most frequent persistent symptom following cancer treatment. This article aims at explaining how the implementation of contemporary pain neuroscience can benefit rehabilitation for adults following cancer treatment within an evidence-based perspective. Materials and methods: Narrative review. Results: First, pain education is an effective but underused strategy for treating cancer related pain. Second, our neuro-immunological understanding of how stress can influence pain highlights the importance of integrating stress management into the rehabilitation approach for patients having cancer-related pain. The latter is supported by studies that have examined the effectiveness of various stress management programmes in this population. Third, poor sleep is common and linked to pain in patients following cancer treatment. Sleep deprivation results in a low-grade inflammatory response and consequent increased sensitivity to pain. Cognitive behavioural therapy for sleep difficulties, stress management and exercise therapy improves sleep in patients following cancer treatment. Finally, exercise therapy is effective for decreasing pain in patients following cancer treatment, and may even decrease pain-related side effects of hormone treatments commonly used in cancer survivors. Conclusions: Neuro-immunology has increased our understanding of pain and can benefit conservative pain treatment for adults following cancer treatment. Implications for Rehabilitation: Pain education is effective for improving cancer pain; implementation of contemporary pain neuroscience into the educational programme seems warranted. Various types of stress management are effective for treating patients following cancer treatment. Poor sleep is common in patients following cancer treatment, and rehabilitation specialists can address this by providing exercise therapy, sleep hygiene, and/or cognitive behavioural therapy. Exercise therapy is effective for decreasing pain in patients following cancer treatment, including the treatment of pain as a common side effect of hormone treatments for breast cancer survivors.